Analisis Daya Dukung dan Penurunan Pondasi Tiang Bor Pada Struktur Kepala Jembatan - Januar, Galang Rasyid; Agung, Putera Agung Maha (Indonesian Society of Applied Science, 2023)
The foundation is an important part of the building, especially on the bridge that serves to withstand the load either its own weight or the load that works on it. The bearing capacity of the soil is the main support for a foundation as a component that transmits the load acting on the soil. Based on the results of the analysis of the bearing capacity of the drilled head of the bridgehead of the X toll road project, which was planned by the author with a configuration of 15 poles with a diameter of 100 cm at a depth of 20 m, the Ascial bearing capacity of 207,703 for single piles and 2429,674 tons for groups was obtained based on the Resse and Wright method. Meanwhile, the lateral bearing capacity is 249,206 tons for single-clamp conditions and 2915,159 tons for group piles using the Broms method. The decrease that occurred was 1,805 cm for single piles and 2,199 cm for group piles, and based on the calculation of stability, the configuration was said to be stable to withstand the working load.